Accidents in speleology: Analysis of major risks and preventive measures (Research, Society and Development, 2025)
Objective: To identify the most common accidents in speleology and their prevention measures, collect statistical data on rescues, and determine the most common risk factors among sports enthusiasts. Method: Systematic Literature Review using the PubMed and BVS databases. The PIO structure was used to outline the components of the research question, and the PRISMA method was employed for article selection. We selected articles published between 1999 and 2022. Results: The most common accidents are falls, collapses, and floods, with the incidence of rescues varying by country. Risk factors include a lack of training and knowledge in rescue and first aid, as well as the absence of the use of personal protective equipment (PPE). Conclusions: The most common accidents in speleology are falls, collapses, and floods, which are often severe but preventable. Continuous safety training and interdisciplinary research are essential to reduce risks and enhance safety in this sport.